2010
DOI: 10.1590/s0104-77602010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Evapotranspiration and estimation of aerodynamic and stomatal conductance in a fragment of Atlantic Forest in mantiqueira range region, MG

Abstract: Understanding hydrologic behavior in forested areas, not least the Brazilian Atlantic Forest, is of fundamental importance for environmental modeling. This work aimed to estimate evapotranspiration values in Atlantic Forest remnants of Mantiqueira Range region using water balance calculations, and to estimate parameters (stomatal and aerodynamic conductances) for this vegetation cover using the Penman-Monteith model. In terms of water balance, evapotranspiration accounted for 89% of total precipitation, deep p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…The increase in evapotranspiration in the scenarios with the highest percentage of native forest is mainly due to the higher leaf area index (LAI) of this type of vegetation, increasing the tree canopy -environment gas exchange (Pereira et al, 2010 volume explored by the forest roots increases water availability, resulting in higher consumption by forest vegetation. Water availability in the soil also increased with the introduction of conservation areas, as shown by the increased mean annual variation in soil water storage (∆θ), which was 8.5 mm for scenario C1 and 6.2 mm for C0 (Figure 4), contributing to an increase in evapotranspiration and reduction in annual runoff.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in evapotranspiration in the scenarios with the highest percentage of native forest is mainly due to the higher leaf area index (LAI) of this type of vegetation, increasing the tree canopy -environment gas exchange (Pereira et al, 2010 volume explored by the forest roots increases water availability, resulting in higher consumption by forest vegetation. Water availability in the soil also increased with the introduction of conservation areas, as shown by the increased mean annual variation in soil water storage (∆θ), which was 8.5 mm for scenario C1 and 6.2 mm for C0 (Figure 4), contributing to an increase in evapotranspiration and reduction in annual runoff.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the water storage in the soil, annual average variations of 17.03 and 9.83 mm were simulated, equivalent to 1.3 and 0.7% of the total water balance, for the calibration and validation periods, respectively. Pereira et al (2010) performed the water balance in an Atlantic Forest area of a basin located in the region of the Mantiqueira Range, Brazil, on the basis of measurements made in the field. The authors found that evapotranspiration corresponded to 89%, percolation to 12.1% and storage to −1.1% of the water balance.…”
Section: Tablementioning
confidence: 99%
“…In the Atlantic Forest, a fragment of forest had average g a of 0.099 m s -1 (Pereira et al, 2010), higher than other tropical forests.…”
Section: Conductance Aerodynamicsmentioning
confidence: 89%